An agricultural approach to the commercialization of cash waqf between Malaysia and Nigeria - Amuda, Yusuff J.; Che Embi , Nor Azizan; Babat, Oladapo H. (Journal of Advanced Management Science, 2014)
The Nigeria agricultural sector is faced with many unprecedented problems including loss of focus, abandonment, and inadequate motivation to farmers. This shocking situation has deprived Nigerians of abundant food at affordable prices. In addition, employment in this sector is at an all-time low. The root cause of this problem is the complete abandonment of the sector by both past and present governments. Though Nigeria introduced agricultural programs such as Operation Feed the Nation, however, the outcome has not been impressive. The purpose of this research is to examine the possibility of transfer of funds from waqf institutions in Malaysia to institutions in Nigeria. The agricultural commercialization of cash waqf between Malaysia and Nigeria would not only ensure food security but also employment and productive use of idle land. While existing literatures have focused on the transformation of the poor, there is a dearth of study that analyses institutional transfer of funds for boosting agricultural studies from one country to the other. The findings show that the waqf institution can play an important role in building a good relationship between one country and the other, create jobs, economically transform impoverished youths, and enable the elderly. Nigeria excelled in agricultural activities in the sixties and seventies before the sector was neglected due to the discovery of crude oil. Furthermore, the restoration of past glory is ensured as well as the bridging of the gap between the urban and rural dwellers. This paper employs a qualitative approach and survey of literature. The paper suggests that through this approach, social vices among unemployed youths will be drastically reduced in the society.